Genetic variants in COL11A2 of lumbar disk degeneration among Chinese Han population. Issue 2 (8th December 2018) - Yang, Xuejun; Jia, Haiyu; Xing, Wenhua; Li, Feng; Li, Manglai; Sun, Ke; Zhu, Yong
Abstract: Background: Lumbar disk disease (LDD) is a common musculoskeletal disorder. Several predisposing genetic and environmental risk factors have been established for symptomatic LDD. Methods: We conducted a case–control association study to investigate the role of the COL11A2 gene in LDD. Genotyping of 384 Chinese Han LDD patients and 384 Chinese Han controls was made for six single‐nucleotide polymorphisms (SNPs) from COL11A2 by Agena Massarray. We evaluated these SNPs association with LDD using the chi‐square test and genetic model analysis. Results: The strongest associations with LDD were observed for polymorphisms in rs2071025. Carriers of "A" allele had an increased risk of LDD (OR = 1.47, 95% CI = 1.20–1.80, p  = 0.0002) as compared with the "G" allele in allele model. We found that rs2071025 were associated with LDD in female and male from the stratification analyses ( p  < 0.05). Genetic models showed that rs986522(C) significantly increased the risk of LDD in female; however, in males, we did not find significant associations between the rs986522 and LDD risk. Conclusion: This study showed a genetic association with COL11A2 polymorphism in individuals with LDD. These data may provide novel insights into the pathogenesis of LDD, although further studies with larger numbers of participants worldwide are needed for validation of our conclusions. Abstract : We conducted a case–control association study to investigate the role of the COL11A2 gene in LDD. Our results suggest that the rs2071025 G allele plays a minor role in LDD of the Chinese Han population.